Configurable three-dimensional boron nitride-carbon architecture and its tunable electronic behavior with stable thermal performances - Loeblein, Manuela (2014)
Recent developments of 3D-graphene and 3D-boron-nitride have become of great interest owing to their potential for ultra-light flexible electronics. Here we demonstrate the first synthesis of novel 3D-BNC hybrids. By specifically controlling the compositions of C and BN, new fascinating properties are observed, such as highly tunable electrical conductivity, controllable EMI shielding properties, and stable thermal conductivity. This ultra-light hybrid opens up many new applications such as for electronic packaging and thermal interface materials (TIMs).